ROLE OF α ↔ γ TRANSFORMATION IN IRON IN THE FORMA- TION OF SURFACE LAYER ON IT - Мельник, Петро Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Conception of vacancy mechanism of forming of the alloyed superficial layer on iron is examined, being based on existence in him of natural polymorphic transformation of α↔γ at 910 oС.